Familial occurrence of bipolar disorder – review - Perzyński, Adam; Karakuła, Hanna; Masiak, Jolanta; Kozak, Gustaw; Krasowski, Tomasz (Current Problems of Psychiatry, 2012)
Since the very origin of Emil Kraepelin’s concept of recurrent psychoses the knowledge concerning affective disorders has developed significantly. Nowadays bipolar disorder is a separate disease and it is still not sure if we deal with a single illness or with many ones resembling each other. Basing on clinical course, four types of bipolar disorders are presently distinguished. They differ significantly and have tendency to familial occurrence. This familial occurrence may be sometimes a key to better and quicker diagnosing of disturbances occurring in children and adolescents. Atypical symptoms of bipolar disorder in the young are rather a rule than an exception. Symptoms leading to diagnosing of ADHD or conduct disorder may be early forms of affective disturbances. Even if not, their over incidental co-occurrence should lead psychiatrists to monitor any signs of affective disorder. The additional fact is that diagnosis of bipolar disorder is usually given between 16-25thyear of life. Therefore it is very important to know, as precisely as possible, the family history of any psychiatric disturbances. Data show that cases of bipolar disorder but also other mood disturbances and drug or alcohol abuse, conduct disorder, attention deficiency hyperkinetic disorder, personality disturbances, anxiety disturbances including panic ones, should be perceived as bipolar spectrum disorder. In this review of literature we analyze subtypes of bipolar disorder, comorbidity, clinical connections and familial correlations.